An Advanced Study on Increasing Incidence of Diabetes Mellitus, Systemic Hypertension and Germ Cells with Endogenous Estrogen - Samuel, Elizabeth Jeya Vardhini (Highlights on Medicine and Medical Research Vol. 2, 2021)
Background: Era of contraception, abortions, [20th, 21st centuries] implemented as family welfare schemes, witnessed increased global incidence of Type 2 diabetes mellitus, systemic hypertension. Global incidence of diseases including diabetes mellitus, systemic hypertension was rising; hence an altruistic analysis was planned to assess, if any correlation existed with contraception and rising incidence of diseases namely diabetes mellitus, systemic hypertension. Objectives: Altruistic association of contraception [if any], with increasing diabetes mellitus, systemic hypertension, was sought after. Methods: In 2012, retrospective analysis of, prevalence of diabetes mellitus, systemic hypertension, in 350 patients of 20 - 35 years, 35 - 50 years, >50 years, age groups, data collected by convenient, stratified random sampling, from different geographical locations, between 2003-2012 and its association with presence, absence of contraception, abortion was undertaken; simultaneously, serum estrogen levels obtained from 105 patients, were also analysed. Results: 10 - 45 fold increase in Type 2 diabetes mellitus was seen in contraceptive users of >20 years to >50 years; 15 - 50 fold increase in incidence of systemic hypertension was seen in contraceptive users of >20 years to >50 years. Endogenous estrogen was reduced below normal in 75% of contraceptive users, and 25% of contraceptive users had low normal serum estrogen. Cholesterol deprived diet, due to decreased synthesis of endogenous estrogen, androgen also was associated with 50% increase in diabetes mellitus, systemic hypertension. Conclusion: Concept is acquired contraception, abortion status, with smashed fragmentation of germ cells, reduced endogenous estrogen, androgen, results in defaulted genomic repertoire, deranged cell metabolism, increased incidence of diabetes mellitus, systemic hypertension as part of metabolic syndrome. Contraception reversal declined the diseases as a cause and effective phenomenon.